Dietary Habits and Prevalence of Allergic Rhinitis in 6 to 7-Year-Old Schoolchildren in Turkey - Zeynep Tamay; Ahmet Akcay; Ahmet Ergin; Nermin Güler (Allergology International, 2014)
Background:: The prevalence of allergic rhinitis and other allergies has risen worldwide. Dietary habits are considered to be among the potential risk factors. The aim of this study was to evaluate the prevalence of allergic rhinitis and its relationship with dietary habits and other risk factors among 6 to 7-year-old Turkish schoolchildren. Methods:: In this cross-sectional study, a total of 11483 children aged 6-7 years were surveyed. The prevalence of symptoms of allergic rhinitis was assessed using the ISAAC protocol. Dietary information was collected using a food frequency questionnaire. Results:: Of them, 9875 (50.7% M 49.3% F) questionnaires were appropriately completed. The prevalence rates of lifetime rhinitis, current rhinitis, current rhinoconjunctivitis and physician-diagnosed allergic rhinitis, were 44.3%, 29.2%, 8.5% and 8.1%, respectively. Consumption of rice, and cereals ≥3 times per week showed protective effect on physician-diagnosed allergic rhinitis (aOR = 0.53, 95% CI = 0.32-0.87 and aOR = 0.58, 95% CI = 0.36-0.92). Eating pasta, and chocolates ≥3 times per week showed protective effect on current rhinoconjunctivitis (aOR = 0.45, 95% CI = 0.25-0.79 and aOR = 0.50, 95% CI = 0.29-0.86). Eating lollipops, candies and animal fats ≥3 times per week was positively associated with current rhinoconjunctivitis (aOR = 1.47, 95% CI = 1.00-2.17 and aOR = 2.25, 95% CI = 1.11-4.56). Protective effect of the Mediterranean diet was not significant. Conclusions:: Frequent consumption of cereals, rice, pasta and chocolates may have beneficial effect on symptoms of rhinoconjunctivitis. Although dietary habits may affect the prevalence of symptoms of current rhinoconjunctivitis, the Mediterranean diet alone may not be protective against rhinoconjunctivitis.